2002
DOI: 10.1055/s-2002-25322
|View full text |Cite
|
Sign up to set email alerts
|

Die vaskuläre Komponente: Gedanken zur Entstehung des Angiofibroms

Abstract: Incomplete regression of the first branchial arch artery presenting an atavism is suited to explain the vascular tumour component of angiofibromas considering main tumour characteristics (origin in the posterior nasal cavity close to the sphenopalatine foramen, main blood supply from the maxillary artery with possible feeders arising from the internal carotid artery). Our embryological contributions support to define angiofibromas as vascular malformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 15 publications
0
7
0
3
Order By: Relevance
“…Morphologische Beobachtungen weisen auf die Einordnung als Gefäûmissbildung hin [2], die embryologisch durch einen Atavismus der 1. Pharyngealbogenarterie erklärt werden kann [3].…”
Section: Introductionunclassified
“…Morphologische Beobachtungen weisen auf die Einordnung als Gefäûmissbildung hin [2], die embryologisch durch einen Atavismus der 1. Pharyngealbogenarterie erklärt werden kann [3].…”
Section: Introductionunclassified
“… To perform successful surgery, the specific features of the individual JNA must be considered [ 1044 ], [ 1045 ]. Sense and necessity of preoperative embolization are discussed controversially [ 1044 ].…”
Section: Indications Of Surgery Beyond Chronic Rhinosinusitismentioning
confidence: 99%
“…More recently, immunohistological and electron microscopic studies have suggested that this lesion may be considered a vascular malformation (or hamartoma) rather than a tumor [10]. These observations led Schick and colleagues [11] to postulate that JA might be due to incomplete regression of the first branchial artery, which arises in embryogenesis between days 22 and 24 and forms a temporary connection between the ventral and dorsal aorta. This artery commonly regresses and forms a vascular plexus that either involutes or may leave remnants, potentially leading to development of JA.…”
Section: Histopathological Aspects and Pathogenesismentioning
confidence: 99%
“…Gains at chromosomes 4, 6, 8, and X and losses on chromosomes 17, 22, and Y are the most frequent chromosomal abnormalities detected [11, 2023]. Moreover, Schick [21] described the gene AURKA (20q13.2), a centrosome-associated serine/threonine kinase, with a possible role in chromosomal and genetic instability in JA.…”
Section: Histopathological Aspects and Pathogenesismentioning
confidence: 99%